Strategi Pemasaran Serta Peran Kreativitas dan Inovasi dalam Pengembangan Produk Mouku Cimahi - Tiara Kamilla; Haneti Arumsari; Nathania Nanda Nugraha; Budi Prasetiyo (Jurnal Pemberdayaan Ekonomi, 2023)
Purpose: The purpose of this research is to study and analyze marketing strategies and creativity in Mouku Cimahi Micro, Small and Medium Enterprises (MSMEs) in Cimahi City, West Java Province. Methodology: The method or method used is descriptive qualitative which uses several processes such as observation and interviews, analysis of observation results, providing alternative improvements. Then the informant who was used as a source of data was the owner of the MSME Mouku Cimahi, this research was carried out throughout a period of 3 months. Based on this research method, the strategy that has been tried in research on Micro, Small and Medium Enterprises (MSMEs) Mouku Cimahi is to conduct an analysis carried out in this study is STP (segmentation, targeting, positioning). Results: The results of the study show that MSMEs of Mouku Cimahi have not maximized technology for their marketing, because they have less and limited expertise and are also faced with cases in the development of their business. The cases experienced in Mouku Cimahi include the lack of skilled human resources in the field of technology and product creativity.